Sediment Distribution related to Gold and Silver Placer Deposits in Offshore of Sambas Besar Estuary, Sambas Regency, West Kalimantan - Ediar Usman; I. W. Lugra (Geological Agency, 2011)
DOI: 10.17014/ijog.v6i1.113Result of grain size analysis of the sea floor sediments from the study area indicates four sediment types, those are silt, sandy silt, silty sand, and sand. The silt unit has the widest distribution that is around 127.2 km2, sandy silt 12.65 km2, sand 1.176 km2, and silty sand 0.44 km2. Result of gold and silver content analysis from some selected samples indicates that the highest gold and silver amount are at PMK-08 location in northern part of the study area with gold content of 0.21 ppm and silver 13.36 ppm; both are silt sediment types. The highest gold and silver content occur within medium - coarse sediments containing subrounded grains of quartz and pyrite, at northern part of the study area. The presence of silver and gold is suggested to be controlled by a north-south longshore current pattern. The source of sediments from Sambas Besar River follows the longshore current, e.g. in northern estuary from south to north, and at southern estuary from north to south direction.